2020
DOI: 10.3390/polym12123043
|View full text |Cite
|
Sign up to set email alerts
|

Dope-Dyeing of Polyvinyl Alcohol (PVA) Nanofibres with Remazol Yellow FG

Abstract: The lack of aesthetic properties of electrospun nanofibres in terms of colour appearance is the drive in this preliminary study. This research is conducted to study the dyeing behaviour and colorimetric properties of electrospun nanofibres blended with Remazol Yellow FG reactive dye using dope-dyeing method via electrospinning process. This paper reports the colorimetric properties of dyed poly vinyl alcohol (PVA) nanofibres within the range of 2.5 wt.% to 12.5 wt.% dye content. The electrospinning parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…(7) The correlation between sedation score and stress index of patients undergoing hip replacement is analyzed. (8) The correlation between sedation score and pain degree of patients undergoing hip replacement is analyzed.…”
Section: Observation Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) The correlation between sedation score and stress index of patients undergoing hip replacement is analyzed. (8) The correlation between sedation score and pain degree of patients undergoing hip replacement is analyzed.…”
Section: Observation Indicatorsmentioning
confidence: 99%
“…Rimazolam is a new benzodiazepine designer. This drug is characterized by quick effect, quick recovery and small influence, and can exert sedative effect quickly [ 8 ]. However, the quality of anesthesia induction with different doses of Rimazolam is not uniform, so the selection of appropriate drug dose can greatly improve the stability of circulation in patients during surgery and reduce adverse reactions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Esfahani et al [ ] have prepared red‐BS dye‐doped PVOH and concluded that the red‐BS molecules led to the increase of the absorption coefficient, concomitantly with the decrease of the band gap. More recent research concerning dyed PVOH systems is focused on waveguides, [ 26 ] textile fabrication, [ 27 ] nonlinear optics, [ 28 ] optical limiters, [ 29 ] materials with photoinduced optical anisotropy, [ 30 ] and dye‐sensitized solar cells. [ 31, 32 ] Other important contributions on this subject were made by Dorohoi and collaborators.…”
Section: Introductionmentioning
confidence: 99%
“…A syringe pump was used to deliver the polymer solution from a syringe to the needle at a fixed rate of 0.5 ml/hr. The electrospinning setup was described elsewhere [18][19][20].…”
Section: Introductionmentioning
confidence: 99%